College study skills becoming a strategic learner - Van Blerkom, Dianna L. (Wadsworth college success series., 1994)
This is neither a brief, limited study skills text nor an overwhelmingly comprehensive study skills text. It is mid-range in its coverage of the major topics for study skills and provides principles and practice with a marvelous collection of examples...This is neither a brief, limited study skills text nor an overwhelmingly comprehensive study skills text. It is mid-range in its coverage of the major topics for study skills and provides principles and practice with a marvelous collection of examples...